2024
DOI: 10.1108/ict-11-2022-0084
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of a high commitment work system on well-being: the mediating role of organization support and employee work-life balance

Badreya Alzadjali,
Syed Zamberi Ahmad

Abstract: Purpose This study aims to examine the effect of a high commitment work system (HCWS) on employee well-being and the mediating role of organizational support and work–life balance. Design/methodology/approach Using structural equation modeling (SEM) for analysis, a quantitative approach was adopted to collect data from the 235 employees from the public sector in the United Arab Emirates (UAE). Findings Results show that HCWSs have a significant influence on organizational support and employee work–life bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…The discourse on employee well-being within organizations has evolved significantly over the last decades, reflecting a deeper and more diverse understanding through various perspectives and methodologies. Research has extensively explored the relationship between well-being and aspects of work, including perceived organisational support, workplace spirituality, organizational commitment, and employee engagement, highlighting their critical role (Rhoades & Eisenberger, 2002;Kurtessis et al, 2015;Sharma & Kumra, 2020;Alzadjali, 2024). Gutiérrez et al (2020) demonstrated that various forms of well-being directly correlate with job performance, influenced by multiple factors.…”
mentioning
confidence: 99%
“…The discourse on employee well-being within organizations has evolved significantly over the last decades, reflecting a deeper and more diverse understanding through various perspectives and methodologies. Research has extensively explored the relationship between well-being and aspects of work, including perceived organisational support, workplace spirituality, organizational commitment, and employee engagement, highlighting their critical role (Rhoades & Eisenberger, 2002;Kurtessis et al, 2015;Sharma & Kumra, 2020;Alzadjali, 2024). Gutiérrez et al (2020) demonstrated that various forms of well-being directly correlate with job performance, influenced by multiple factors.…”
mentioning
confidence: 99%